Corrosion inhibition of aluminum in 2M HCL using chromolaena odorata leaf extract - Odadayerewhre, Excel Tega (International Journal of Advanced Chemistry, 2025)
Metal corrosion in acidic conditions, especially aluminum, poses major challenges to the industry and leads to great fiscal loss and safety ‎problems. The development of green corrosion inhibitors has sparked growing interest due to their low toxicity and ‎biodegradability in pursuit of sustainable results. In this research article, we analyze Chromolaena odorata leaf extract as a corrosion ‎inhibitor on aluminum in 2.0 M hydrochloric acid using the weight loss method. The extract shows good inhibitory performance, and ‎inhibition effectiveness increased with concentration. The extract reached a maximum efficiency of 99% at 5% v/v concentration. Adsorption of phytochemicals such as flavonoids and alkaloids onto the aluminum surface, which likely reduces corrosion. The adsorption ‎behavior conformed to the Langmuir isotherm, indicating monolayer adsorption on the metal surface. These findings suggest that ‎Chromolaena odorata can serve as a green alternative to conventional synthetic corrosion inhibitors‎.